Measuring the inequality in education: educational Kuznets curve - Khusaini, Khusaini; Remi, Sutyastie Soemitro; Fahmi, Mohamad; Purnagunawan, Rd. Muhamad (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to measure the inequality of education. The study examines the pattern in the educational Lorenz curve as a way to investigate the impact of education experience, per capita income, and poverty on educational inequality. Using Banten Province secondary data series over 1996 –2016, the unbalanced panel unit root were tested for the educational Kuznets curve. The regression results shows that the educational Kuznets curve does not exist. While we found that the educational experience reduce the educational inequality, the per capita income and poverty were not significant.